Test Case Generator for Visual Programming Language - Jaafar, Mohd Farid (2007)
Designing test cases is a tedious and meticulous work. A tester needs to have a depth understanding of a program before a good test suite can be designed. Sometimes, even an expert tends to miss some test cases. The same scenario applies in designing test cases for Visual Programming Language (VPL). Most studies in designing test cases for VPL are using requirement specification, design specification, complex technique (i.e. Z) and third-party tools that requiring novice user to supply information that is not familiar to them. It is certain that the information supplied in creating test case was less accurate and thus affected the test suite produced. Therefore, this research explores the creation of automated test case generator for a VPL using Extensible Markup Language (XML) based language as data representation. The generation method is based on path coverage and boundary value analysis testing techniques. Validation and verification of the test cases created by the tools is done by comparing the generated test cases with the manually-designed test cases. Five test program are chosen and tested using the propose method. From the result and analysis, a conclusion is drawn that the automated test case generator created are able to create test cases for VPL.